The Interplay Between the Renin-Angiotensin-Aldosterone System and Parathyroid Hormone - Zheng, Ming-Hui; Li, Fu-Xing-Zi; Xu, Feng; Lin, Xiao; Wang, Yi; Xu, Qiu-Shuang; Guo, Bei; Yuan, Ling-Qing (Frontiers in Endocrinology, 2020)
The renin-angiotensin-aldosterone system (RAAS) is the regulatory system by which renin induces aldosterone production. Angiotensin II (Ang II) is the main effector substance of the RAAS. The RAAS regulates blood pressure and electrolyte balance by controlling blood volume and peripheral resistance. Excessive activation of the RAAS is an important factor in the onset of cardiovascular disease and the deterioration of this disease. The most common RAAS abnormality is primary aldosteronism (PA). Parathyroid hormone (PTH) is a peptide secreted by the main cells of the parathyroid gland, which promotes elevated blood calcium (Ca2+) levels and decreased blood phosphorus (Pi) levels. Excessive secretion of PTH can cause primary hyperparathyroidism (PHPT). Parathyroidism is highly prevalent in postmenopausal women and is often associated with secondary osteoporosis. PA and PHPT are common endocrine system diseases. However, studies have shown a link between the RAAS and PTH, indicating a positive relationship between them. In this review, we explore the complex bidirectional relationship between the RAAS and PTH. We also point out possible future treatment options for related diseases based on this relationship.